2015
DOI: 10.1161/hypertensionaha.114.04222
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase in the Renal Microvasculature Is a Primary Target for Blood Pressure–Lowering Effects by Inorganic Nitrate and Nitrite

Abstract: Abstract-Renal oxidative stress and nitric oxide (NO) deficiency are key events in hypertension. Stimulation of a nitrate-nitrite-NO pathway with dietary nitrate reduces blood pressure, but the mechanisms or target organ are not clear. We investigated the hypothesis that inorganic nitrate and nitrite attenuate reactivity of renal microcirculation and blood pressure responses to angiotensin II (ANG II) by modulating nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity and NO bioavailability. Nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
85
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 53 publications
(66 reference statements)
5
85
0
3
Order By: Relevance
“…The absence of somatic motor reflexes in response to tail pitching or blinking in response to a lowpressure corneal stimulation indicated deep anesthesia, and at least 15 minutes of stabilization was allowed before drug infusions. Rats were 42 Arterial rings (2 mm) were mounted on 25-µm tungsten wires in a small-vessel myograph (Model 620M; Danish Myo Technology, Denmark) for recording isometric force by transducers (PowerLab 4/30; AD Instruments). The chambers were filled with Krebs solution (37 °C, pH 7.4) aerated with carbogen (95% O 2 ; 5% CO 2 ).…”
Section: Surgical Procedures and Assessment Of Cardiovascular Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of somatic motor reflexes in response to tail pitching or blinking in response to a lowpressure corneal stimulation indicated deep anesthesia, and at least 15 minutes of stabilization was allowed before drug infusions. Rats were 42 Arterial rings (2 mm) were mounted on 25-µm tungsten wires in a small-vessel myograph (Model 620M; Danish Myo Technology, Denmark) for recording isometric force by transducers (PowerLab 4/30; AD Instruments). The chambers were filled with Krebs solution (37 °C, pH 7.4) aerated with carbogen (95% O 2 ; 5% CO 2 ).…”
Section: Surgical Procedures and Assessment Of Cardiovascular Responsmentioning
confidence: 99%
“…Resting tension of the arteries was set as described previously. 42,43 After stabilization and washout protocols, 1 µmol/L norepinephrine was used to preconstrict mesenteric resistance vessels to obtain a basal tone of ≈50% of its maximal diameter. When the constriction reached a steady-state plateau, sodium nitrite (10 …”
Section: Surgical Procedures and Assessment Of Cardiovascular Responsmentioning
confidence: 99%
“…They showed that inorganic nitrate and nitrite attenuate reactivity of the renal microcirculation and BP responses to angiotensin II by modulating Nox activity and NO bioavailability. 37 In a model of oxidative stress (SOD1 −/− ), abnormal angiotensin II-mediated arteriolar contractions were normalized by nitrite with Nox oxidases as a possible target.…”
mentioning
confidence: 99%
“…9 The authors test the hypothesis that stimulation of a nitrate-nitrite-NO pathway, with inorganic nitrate or nitrite, limits afferent arteriolar responsiveness to Ang II and markedly attenuates Ang II-induced hypertension by inhibiting superoxide production via nitric oxide synthase-independent NO generation ( Figure). The authors show convincingly that Ang II-induced constriction of isolated preglomerular afferent arteriolar ex vivo preparations can be blunted by inorganic nitrite at physiological concentrations as well as through dietary nitrate supplementation.…”
Section: See Related Article Pp 161-170mentioning
confidence: 99%
“…9 Future studies will undoubtedly be aimed at translating these findings to human patients. Interestingly, one cannot but wonder whether xanthine oxidase inhibitors (eg, allopurinol, febuxostat) currently prescribed to treat a variety of uric acid-based disorders (eg, gout) may inadvertently limit nitritederived NO and thereby elevate blood pressure in such individuals.…”
Section: See Related Article Pp 161-170mentioning
confidence: 99%